Effectiveness of Social Media in Education - et. al., M.Sasikala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of social media in education provides students with the ability to get more useful information, to connect with learning groups and other educational systems that make education convenient. Social network tools afford students and institutions with multiple opportunities to improve learning methods. Through these networks, you can incorporate social media plug-in that enable sharing and interaction. Social media is also a medium where students can establish beneficial connections for their careers. This can help students compile and produce useful content for research. Whether students are working on an assignment, working on a project or trying to gain more insight on a subject, some of the best information and results can be extracted from social media. This article deals with effectiveness of social media in education especially its importance, types, uses and how we can use in the classroom..